Pediatric preseptal and orbital cellulitis: A 10-year experience. (May 2019) - Santos, Joana Caldeira; Pinto, Sara; Ferreira, Sofia; Maia, Catarina; Alves, Sandra; da Silva, Vinhas
Abstract: Objective: Characterize clinical features, epidemiology and treatment of hospitalized pediatric cases of preseptal and orbital cellulitis. Methods: Retrospective study of children/adolescents admitted to a central hospital with preseptal and orbital cellulitis between 2007 and 2017. Results: A total of 122 cases were included, 80.3% with preseptal cellulitis and 19.7% with orbital cellulitis. Patients had a median age of 5 years. Sinusitis was the most common predisposing factor (40.2%), followed by dental abscess (20.4%) in preseptal cellulitis and by external ocular infections (12.5%) in orbital cellulitis. Sinusitis (p < 0.001) was associated with orbital cellulitis, whereas patients with dental abscess (p = 0.007) and trauma (p = 0.040) were most likely to have preseptal cellulitis. Fever, photophobia, ocular pain, painful eye movements, proptosis, rhinorrhea and vison impairment were related with orbital cellulitis. Leukocytosis was present in 34.4% of patients, and associated with orbital cellulitis (p = 0.001). Nearly half of patients (49.2%) had a CT-scan performed. Systemic corticosteroids were used in 19.7%. Complications occurred in 13 patients. Imaging revaluation through CT was performed in 6.6%, with no patients showing deterioration; 1.6% of patients required surgery. Conclusions: Identification of orbital involvement signs suggested orbital cellulitis. We emphasize the impact of dental abscess as a predisposing factor for preseptal cellulitis. Repeated imaging had no impact on treatment or outcome. A high percentage of patients was treated with steroids despite their controversial use.